Relationships of beans intake with chronic kidney disease in rural adults: A large-scale cross-sectional study - Yin, Lei; Dong, Xiaokang; Liao, Wei; Liu, Xiaotian; Zheng, Zhaohui; Liu, Dongwei; Wang, Chongjian; Liu, Zhangsuo (Frontiers in Nutrition, 2023)
Background and Aims: Dietary factors play an important role in the development of chronic kidney disease (CKD). However, evidence on the relationship of beans consumption with CKD remains limited and inconclusive, especially in the middle- and low-income populations. The current study aimed to investigate the relationships of beans intake with indicators of kidney injury and CKD prevalence in rural adults. Methods: A total of 20,733 rural adults from the Henan Rural Cohort Study in 2018-2022 were included. The total beans intake was collected using a validated food frequency questionnaire. Indicators of kidney injury and CKD was determined by the estimated glomerular filtration rate and the urinary albumin to creatinine ratio. Generalized linear regression and logistic regression models were applied to estimate the relationship of beans intake with continuous and dichotomized indicators of renal function, respectively. Results: Of the 20,733 participants, 2676 (12.91%) subjects were identified as CKD patients. After adjusting for potential confounders, participants in the higher quartiles of beans intake had a lower prevalence of CKD (odds ratio and 95% confidence interval, OR (95%CI); Q2: 0.968(0.866-1.082); Q3: 0.836(0.744-0.939); Q4: 0.854(0.751-0.970)) and albuminuria (Q2: 0.982(0.875-1.102); Q3: 0.846(0.750-0.954); Q4: 0.852 (0.746-0.973)), compared with the Q1. Per 50g/day increment in beans intake was significantly associated with a 5% and 4% decreased prevalence of albuminuria and CKD, respectively. These inverse relationships were also significant in the subgroups of men, elder, and high-income participants (P<0.05). Conclusion: Dietary beans intake was inversely associated with the prevalence of albuminuria and CKD in rural adults, suggesting that promoting soy food intake might help reduce the occurrence of CKD in rural adults.